DOI: 10.33915/etd.5887
|View full text |Cite
|
Sign up to set email alerts
|

Design and Development of a Twisted String Exoskeleton Robot for the Upper Limb

Abstract: Design and Development of a Twisted String Exoskeleton Robot for the Upper Limb Lei Jiang High-intensity and task-specific upper-limb treatment of active, highly repetitive movements are the effective approaches for patients with motor disorders. However, with the severe shortage of medical service in the United States and the fact that post-stroke survivors can continue to incur significant financial costs, patients often choose not to return to the hospital or clinic for complete recovery. Therefore, robot-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 64 publications
(130 reference statements)
0
0
0
Order By: Relevance
“…The evolution of middle-level mechanical architectures in exoskeletal design has transitioned from an initial emphasis on rigid materials to an increasingly prevalent integration of flexible or hybrid materials, encapsulating advancements in driving methods, structural flexibility, and material transformation. Regarding driving methods, beyond conventional hydraulic, pneumatic, and motor-driven mechanical systems, contemporary developments have introduced cost-effective and lightweight alternatives, such as the twisted rope drive [18] and twisted tube drive [19] integrated into lower limb exoskeleton devices. Studies have suggested that the international exploration of these methodologies commenced around 2017, with domestic Chinese initiatives gaining by 2020.…”
Section: Figure 2 Exoskeleton Thesis Abstract Correlationmentioning
confidence: 99%
“…The evolution of middle-level mechanical architectures in exoskeletal design has transitioned from an initial emphasis on rigid materials to an increasingly prevalent integration of flexible or hybrid materials, encapsulating advancements in driving methods, structural flexibility, and material transformation. Regarding driving methods, beyond conventional hydraulic, pneumatic, and motor-driven mechanical systems, contemporary developments have introduced cost-effective and lightweight alternatives, such as the twisted rope drive [18] and twisted tube drive [19] integrated into lower limb exoskeleton devices. Studies have suggested that the international exploration of these methodologies commenced around 2017, with domestic Chinese initiatives gaining by 2020.…”
Section: Figure 2 Exoskeleton Thesis Abstract Correlationmentioning
confidence: 99%